2020
DOI: 10.1111/jam.14951
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilisCP4, isolated from native soil in combination with arbuscular mycorrhizal fungi promotes biofortification, yield and metabolite production in wheat under field conditions

Abstract: Aims The aim of this study was to identify the best combination of plant growth promoting bacteria (PGPB) and arbuscular mycorrhizal fungi (AMF) for biofortification and enhancing yield in wheat as well as improve soil health under field conditions. Another aim was to get insights into metabolite dynamics in plants treated with PGPB and AMF. Methods and Results Different combinations of PGPB and AMF that gave good results in greenhouse study were used in a field study. The combined application of Bacillus subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 74 publications
4
34
0
3
Order By: Relevance
“…Table 4 shows examples of the beneficial interaction between PGPR and AMF to boost plant growth. The efficacy of co-inoculation of AMF and PGPR have been shown in sorghum [ 160 ], wheat [ 161 , 162 ], swamp oak [ 163 ], bean [ 164 ], and watermelon [ 146 ], and several other plants to promote growth and/or improve stress tolerance. Although an increase in plant growth and grain yield was observed when PGPR and AMF are used in combination, several factors such as environmental conditions, soil quality, and the microbial strains used, contribute to variable results.…”
Section: Co-inoculation Of Amf and Pgpr Can Mitigate The Effects Of Salinity In Plantsmentioning
confidence: 99%
“…Table 4 shows examples of the beneficial interaction between PGPR and AMF to boost plant growth. The efficacy of co-inoculation of AMF and PGPR have been shown in sorghum [ 160 ], wheat [ 161 , 162 ], swamp oak [ 163 ], bean [ 164 ], and watermelon [ 146 ], and several other plants to promote growth and/or improve stress tolerance. Although an increase in plant growth and grain yield was observed when PGPR and AMF are used in combination, several factors such as environmental conditions, soil quality, and the microbial strains used, contribute to variable results.…”
Section: Co-inoculation Of Amf and Pgpr Can Mitigate The Effects Of Salinity In Plantsmentioning
confidence: 99%
“…For example, in all tissues, the contents of N and K were higher along with a higher abundance of Bacillus spp. In contrast, Fe content was higher in the root but lower in leaves when having more Bacillus spp; however, the complex and different regulation of nutrient content in different wheat tissues by microbial inoculants are frequently reported in previous studies (13,(22)(23)(24)43).…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, the relative abundance of WR10 is always much higher in the root than in the sprout at the same time point and effective colonization of AMF, as well as other PGPB, has also been reported in the root of wheat (24,44); however, this experiment provided more information regarding the quantitative or dynamic distribution of microbial inoculants in different tissues of wheat. It was also shown that exogenous WR10 reached a plateau in both the root and the sprout after a certain number of hours (e.g., 10 or 12 hpi).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations